2020
DOI: 10.1101/2020.05.29.123513
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CD147 (BSG) but notACE2expression is detectable in vascular endothelial cells within single cell RNA sequencing datasets derived from multiple tissues in healthy individuals

Abstract: Coronavirus disease 2019 is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and is associated with a wide range of systemic manifestations.Several observations support a role for vascular endothelial dysfunction in the pathogenesis including an increased incidence of thrombotic events and coagulopathy and the presence of vascular risk factors as an independent predictor of poor prognosis. It has recently been reported that endothelitis is associated with viral inclusion bodies suggestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…Human ACE2 is considered an important entry receptor for SARS-CoV-2 [ 76 , 101 , 102 ] and was previously reported to be widely expressed in the lung, vascular system and other organs [ 103 ]. However, a recent study demonstrated that ACE2 is expressed at very low levels and only in a small subset of lung epithelial cells [ 104 ] and low-to-undetectable levels in endothelial cells [ 105 ]. In agreement with the recent observations, our analysis of ACE2 mRNA through the Human Expression Atlas revealed that ACE2 is highly expressed only in intestinal tissues (small intestine, colon and duodenum) and at the low levels in the hearth muscles, kidney, gallbladder and testis, but undetectable in lung ( Figure 4 D).…”
Section: Expression Profile Of Cd209l Family Proteins In Human Tismentioning
confidence: 99%
“…Human ACE2 is considered an important entry receptor for SARS-CoV-2 [ 76 , 101 , 102 ] and was previously reported to be widely expressed in the lung, vascular system and other organs [ 103 ]. However, a recent study demonstrated that ACE2 is expressed at very low levels and only in a small subset of lung epithelial cells [ 104 ] and low-to-undetectable levels in endothelial cells [ 105 ]. In agreement with the recent observations, our analysis of ACE2 mRNA through the Human Expression Atlas revealed that ACE2 is highly expressed only in intestinal tissues (small intestine, colon and duodenum) and at the low levels in the hearth muscles, kidney, gallbladder and testis, but undetectable in lung ( Figure 4 D).…”
Section: Expression Profile Of Cd209l Family Proteins In Human Tismentioning
confidence: 99%
“…is widely expressed in the lung, vascular system and other organs 14 , a recent study demonstrated that ACE2 is expressed at very low levels and only in a small subset of lung epithelial cells 15 and low-toundetectable levels in endothelial cells 16 , suggesting that SARS-CoV-2 entry into and infection of certain human cells may be occurring via alternative receptors or a combination of multiple receptors and/or enhancers Consistent with this idea, Neuropilin receptors [17][18] , CD147/Basigin 19 and heparin sulfate 20 are reported to facilitate SARS-CoV-2 entry. Neuropilin receptors are highly expressed in endothelial and neuronal cells, and play major roles in vascular endothelial growth factor (VEGF)-dependent angiogenesis and semaphorin-dependent axon guidance 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in addition to ACE2, several other membrane components have been proposed to function as co-receptors or attachment sites for SARS-CoV and SARS-CoV-2. These include Cluster of Differentiation 147 (CD147), also known as Basigin (BSG) [ [242] , [243] , [244] , [245] ], Dendritic Cell-Specific Intercellular adhesion molecule-3-Grabbing Non-integrin (DC-SIGN), also known as Cluster of Differentiation 209 (CD209) [ [246] , [247] , [248] , [249] , [250] , [251] ], Neuropilin-1 [ 252 , 253 ], glycosaminoglycans [ 254 ], heparan sulphate [ 255 ], and kidney injury molecule-1 [ 256 ]. Interestingly, in reconstituted lipid membranes devoid of ACE2, binding of the S1 subunit of SARS-CoV-2 spike protein to neutral phospholipid membranes and liposomes was reported to cause mechanical destabilization and membrane permeabilization in a receptor-independent manner [ 257 ].…”
Section: Low Levels Of Lung Expression Of Ace2 and Accessory Proteinsmentioning
confidence: 99%